Pensar una geopolítica y una seguridad decolonial desde África y la Diáspora. - Neiva de Sousa, Laís Cristina (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
This article critically reflects on the construction of a decolonial geopolitics and international security grounded in African and diasporic experiences and epistemologies. The right to development, conceived as both a moral imperative and a strategic instrument, is presented as the central axis. It argues that historical justice, collective memory, and reparations constitute the pillars of a new paradigm of security. Engaging in dialogue with decolonial authors and concrete examples, the article exposes the limits of Eurocentric models of reconstruction and development, proposing alternatives based on sovereignty, solidarity, and equitable cooperation.